Percutaneous thrombectomy of Impella‐associated iliac artery thrombosis using the FlowTriever system. Issue 12 (18th August 2020) - Said, Ahmad; Sayed, Luay
Abstract: Percutaneous thrombectomy using the FlowTriever system is a potentially safe and effective alternative to surgery in cases of Impella‐associated peripheral arterial thrombosis. Abstract : Percutaneous thrombectomy using the FlowTriever system is a potentially safe and effective alternative to surgery in cases of Impella‐associated peripheral arterial thrombosis.